Cambio organizacional y percepción de la justicia organizacional en una entidad de la ciudad de Bogotá-Colombia (2014)
The purpose of this research was to determine the relationship between perceived organizational justice and organizational change in a sample of 80 employees of a company of the defense sector in Bogota, by using a justice (Colquitt, 2001) and an organizational change measure (Grace & Forero 2010). Data analysis was performed using SPSS statistical software. The results indicated significant relationships and associations between organizational change and procedural, informative and interactional justices, but no correlation with distributive justice. The variable projection and development of change showed the highest correlation with the level of total justice in the organization, showing the approach to decision-making and talent management policies that senior management need to implement as a function of the organizational culture that the organization wants to reach.